2012
DOI: 10.1038/ajh.2012.117
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure, Blood Flow, and Atherosclerosis

Abstract: See Original cOntributiOn page 1055B lood vessels are exposed to two kinds of dynamic mechanical forces. One of them is shear stress and the other is the cyclic strain of the vascular wall, which, according to the Laplace's law, is mainly determined by cyclic change of blood pressure (BP). While shear stress directly affects endothelial cells, BP changes (and the resulting changes in arterial wall strain) influence all structures of the arterial wall. Arteries are permanently exposed to a basal stretch, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Obesity is related with hypertension [5,6,7,8].Obesity will trigger the occurrence of hypertension because if a person's body weight increases then the volume of blood also increases so the burden of the heart to pump blood also increases [9]. Fat accumulation due to obesity raises plaque that will clog the blood flow so that blood pressure increases [4,10].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is related with hypertension [5,6,7,8].Obesity will trigger the occurrence of hypertension because if a person's body weight increases then the volume of blood also increases so the burden of the heart to pump blood also increases [9]. Fat accumulation due to obesity raises plaque that will clog the blood flow so that blood pressure increases [4,10].…”
Section: Resultsmentioning
confidence: 99%
“…Increased PP could accelerate the process of atherosclerosis, and vice versa, forming a vicious circle [ 21 ]. Increased PP exerts greater shear stress on arteries, accelerates degeneration of elastic fibers and fracture, promotes the occurrence and rupture of aneurysm and intimal damage and endothelial dysfunction, and induces atherosclerosis and thromboembolic events [ 3 , 22 ]. Thus, PP not only has a very close relationship with arterial stiffness, but also a reflection of accumulated damage on vessels exerted by risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that pulse pressure (PP) is a strong independent predictor of cardiovascular diseases [ 2 4 ]. Elevated pulse pressure has been shown to be a late manifestation of reduced arterial elasticity, which is an important aspect of the arteriosclerosis diagnosis [ 3 ]. However, certain differences exist between blood pressure (BP) of human four limbs as well as PP [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As arteries narrow, the velocity of the blood increases to maintain continual flow. Subsequently, an increase of the velocity creates higher levels of pressure [72,73]. Blood pressure continually places VSMCs under triaxial loading composed of two tensile strains (hoop and axial) and one compressive strain (radial).…”
Section: Mechanical Influence On Arterial Tissues Under Pathological mentioning
confidence: 99%